782 RATIONALE AND DESIGN OF EFI-CHF (ENDOTHELIAL FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE TREATED BY SGLT2I)STUDY. (15th December 2022) - Di Nunno, Nicola; D´alessandro, Damiano; Granatiero, Michele; Tricarico, Lucia; Mazzeo, Pietro; Ceci, Vincenzo; Amatruda, Marco; Pugliese, Rosanna; Alfieri, Simona; Croella, Francesca; Mallardi, Adriana; Leopizzi, Alessandra; et al.
Abstract: Background: Chronic heart failure (CHF) is characterized by endothelial dysfunction (ED). Sodium-glucose cotransporter type 2 inhibitors (SGLT-2i) represent a unique class of anti-hyperglycemic agents for type 2 diabetes mellitus (T2DM) that selectively inhibit renal glucose reabsorption, thereby increasing urinary excretion of glucose. Several studies have demonstrated the cardioprotective effects of SGLT-2i in patients with heart failure (HF), unrelated to its glucosuric effect. Nevertheless, it is unclear whether the benefits of SGLT-2i therapy also rely on the endothelial function in patients with CHF. Aim of the study: To evaluate the effect of SGLT-2i on endothelial function through flow-mediated dilatation (FMD) in patients with CHF at baseline and after 3 months. Design and Methods: EFI-CHF is a multi-center, prospective study that will evaluate the effect of SGLT-2i on endothelial function in patients with chronic stable heart failure across the left ventricular ejection fraction (LVEF) spectrum. Patients with NYHA class II/III symptoms, eGFR> 25 mL/min/1.73 m 2, age >18 years will be enroll. Exclusion criteria are type 1 diabetes mellitus (T1DM), previous amputation surgery, recurrent urinary tract infections. For each patient medical history, clinical and biochemistry data will be collected. Starting treatment with SGLT2 inhibitors will be included. All patients will undergo FMD in an ambulatory setting, at time of enrolment and after 3 months of begin of study. Results: The primary endpoint will be the improvement of endothelial function as assessed by FMD. An univariate and multivariate analysis will be performed to search for predictors of improvement of endothelian function. Conclusions: The EFI-CHF will determine whether SGLT2i therapy improves endothelian function in patients with CHF starting SGLT2i therapy.